European governance and supranational institutions : making states comply - Tallberg, Jonas (Routledge, 2003)
Examines the influence of the European Commission and the European Court of Justice in the political and legal enforcement of member state compliance in the EU.
Keywords: Law -- European Union countries.; Sanctions (Law) -- European Union countries.; Law enforcement -- European Union countries.; Europe -- Economic integration.; Sanctions (Droit) -- Pays de l'Union européenne.; Lois -- Application -- Pays de l'Union européenne.; Europe -- Intégration économique.; LAW -- International.; International economic integration; Law; Law enforcement; Sanctions (Law); Europe; European Union countries; Rechtshandhaving.; Rechtbanken.; Europese Unie.; Europees recht.; Nationaal recht.; EU-landen.; Lagstiftning -- EU-länderna.